Novel PRRT2 mutations in paroxysmal dyskinesia patients with variant inheritance and phenotypes. (21st December 2012) - Liu, X.‐R.; Wu, M.; He, N.; Meng, H.; Wen, L.; Wang, J.‐L.; Zhang, M.‐P.; Li, W.‐B.; Mao, X.; Qin, J.‐M.; Li, B.‐M.; Tang, B.; et al.
Abstract : Paroxysmal dyskinesias (PDs) are a group of episodic movement disorders with marked variability in clinical manifestation and potential association with epilepsy. PRRT2 has been identified as a causative gene for PDs, but the phenotypes and inheritance patterns of PRRT2 mutations need further clarification. In this study, 10 familial and 21 sporadic cases with PDs and PDs‐related phenotypes were collected. Genomic DNA was screened for PRRT2 mutations by direct sequencing. Seven PRRT2 mutations were identified in nine (90.0%) familial cases and in six (28.6%) sporadic cases. Five mutations are novel: two missense mutations (c.647C>G/p.Pro216Arg and c.872C>T/p.Ala291Val) and three truncating mutations (c.117delA/p.Val41TyrfsX49, c.510dupT/p.Leu171SerfsX3 and c.579dupA/p.Glu194ArgfsX6). Autosomal dominant inheritance with incomplete penetrance was observed in most of the familial cases. In the sporadic cases, inheritance was heterogeneous including recessive inheritance with compound heterozygous mutations, inherited mutations with incomplete parental penetrance and de novo mutation. Variant phenotypes associated with PRRT2 mutations, found in 36.0% of the affected cases, included febrile convulsions, epilepsy, infantile non‐convulsive seizures (INCS) and nocturnal convulsions (NC). All patients with INCS or NC, not reported previously, displayed abnormalities on electroencephalogram (EEG). No EEG abnormalities were recorded in patients with classical infantile convulsions and paroxysmal choreoathetosis (ICCA)/paroxysmal kinesigenic dyskinesia (PKD). Our study further confirms that PRRT2 mutations are the most common cause of familial PDs, displaying both dominant and recessive inheritance. Epilepsy may occasionally occur in ICCA/PKD patients with PRRT2 mutations. Variant phenotypes INCS or NC differ from classical ICCA/PKD clinically and electroencephalographically. They have some similarities with, but not identical to epilepsy, possibly represent an overlap between ICCA/PKD and epilepsy . Abstract : Seven PRRT2 mutations (including five novel mutations) in 15 cases (or families) with paroxysmal dyskinesias (PDs) and PDs‐related phenotypes were detected, which extended the spectrum of PRRT2 mutations and provided the evidence that PRRT2 was the causative gene in most familial PDs. The heterogeneity in inheritance patterns of PRRT2 mutations, including autosomal recessive inheritance with compound heterozygous PRRT2 mutations, was identified. Variant phenotypes associated with PRRT2 mutations and EEG abnormalities were reported, including infantile non‐convulsion seizures and nocturnal convulsions that were not reported previously Ethanol induced CTA response varied as a function of age, strain and ethanol dose.